(untitled) (Biomedical Research and Therapy, 2017)
Background: Hemolysis is common in malaria infection and during the course of treatment. Previous studies have reported delayed post-artemisinin hemolysis occurring in naïve and immune individuals treated with parenteral or oral artemisinin-derivatives. This study aims to understand if delayed hemolysis occurs in the absence of malaria parasites and the underlying mechanisms for the hemolytic effects after administration of two antimalarial drugs to malaria-free Wistar rats. Methods: Forty animals were randomized into 5 groups of eight animals each; they received 4 mg/kg artesunate for 7 days (AS), 4 mg/kg artesunate plus 10mg/kg amodiaquine for 3 days (ASQ), 10mg/kg amodiaquine for 3 days (AQ), distilled water [normal control], (Control) and 1mg/kg phenylhydrazine for 1 day to induce hemolysis (PHZ) groups respectively. Packed cell volume (PCV), white blood cell differential count and serum haptoglobin (Hpt) levels were determined in all groups on day 4 and 18 to detect hemolysis. Mean values were compared using t-test and ANOVA with p values <0.05 taken to be significantly different. Results: Post-treatment mean PCV on day 4 was significantly lower than day 18 in all groups except AS group which had similar PCV all through evaluation. Although AQ had lowest mean PCV on day 4, by day 18, mean PCV returned to normal and hpt levels was significantly higher than AS and ASQ groups (p<0.001). Hpt level (mean ± sem) for AS, ASQ, AQ, and control on day 18 were: 18.67 ± 0.004, 50.66 ± 0.014, 73.06 ± 0.003, and 74.13 ± 0.032 mg/dl respectively (p < 0.0001). On day 18, AS and ASQ had significantly lower Hpt level compared to day 4 (p <0.001). No neutropenia was observed during the study. Conclusion: Artesunate induces delayed hemolysis in malaria-free animals possibly through an oxidative toxic effect on the red blood cell membrane. Delayed post-treatment hemolysis was not observed with artesunate-amodiaquine or amodiaquine alone.